Rural clergy of the Pskov region in the first post-war years (1945–1948) - Obozny Konstantin P. (Вестник Свято-Филаретовского института, 2023)
The article covers the situation of the rural Orthodox clergy of the Pskov region in the first post-war years. Based on the documents of the Council for the Affairs of the Russian Orthodox Church and the annual diocesan reports, the main statistical indicators were identified: the number of registered clergymen, their age, period of church service, and level of education. The specificity of the ministry of rural clerics related to issues of economic, legal, ideological nature, is shown. The range of difficulties encountered by Orthodox clergy in the period of the relatively loyal attitude of the Soviet state towards religious organisations is described. The particular specificity of the church situation in the Pskov region is determined by the fact that some territories of the Estonian and Latvian Republics became part of the Pskov region in the post-war period. These areas were distinguished by a high level of church-going of the rural population, the desire to preserve Orthodox traditions. This complicated the work of the authorized Council for the Affairs of the Russian Orthodox Church in the Pskov region, which was aimed at controlling and limiting the influence of religious organizations on Soviet citizens, including those living in the conditions of the Soviet countryside.